Wartime Globalization in Asia, 1937–1945, Conflicted Connections, and Convergences. (12th January 2018) - FROST, MARK RAVINDER; SCHUMACHER, DANIEL
Abstract : Given war's propensity for trampling over and demolishing borders—its literal, one might even say primordial, function as a motor of deterritorialization and reterritorialization—the scant scholarly attention paid to it as a globalizing force remains surprising. An extensive body of literature has responded to the complex role of globalization in the making, as well as the supposed unmaking, of conflict. Liberal economists and political theorists, in an intellectual lineage that dates back to the writings of the European Enlightenment, have made bold claims about global economic integration and the emergence of a 'capitalist peace'. Critics of their arguments have pointed to the Western imperial violence which, from the mid-eighteenth century on, cleared the ground (and perhaps, more importantly, the seas) to make way for the so-called 'free' market world economy, a process which established several of those fundamental worldwide inequalities that have been perpetuated to this day. The hard evidence of a more recent past makes a mockery of the presumption that global capitalist enterprises such as Starbucks and McDonalds might bring about some kind of Big Mac and Frappuccino-mediated universal fraternity. Critical observers of globalization during the 'Noughties' (2000–2010) now recognize it as both one of the most interconnected decades in world history, and also one of the bloodiest.